Layered perovskites Sr3LnBIIITiO8 (BIII – Sc, In) - Titov, Yu. A.; Belyavina, N. M.; Markiv, V. Ya.; Slobodyanik, M. S.; Polubinskii, V. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The scandatotitanates Sr3LnScTiO8 (Ln – La, Pr, Nd, Sm, Eu) and indatotitanates Sr3LnInTiO8 (Ln – La, Pr, Nd) with monoslab layered perovskite-like structures (LPS) have been synthesized by the thermal treatment of a mixture Sr2TiO4 and SrLnBIIIO4 (BIII – Sc, In). The LPS of Sr3LnInTiO8 (Ln – La, Pr, Nd) have been determined by X-ray powder diffraction. It is found that the LPS of Sr3LnInTiO8 (Ln – La, Pr, Nd) belong to the SrLaInO4-type structure (sp. gr. Pbca). The final RB values are equal to 0.055 (Ln – La), 0.062 (Ln – Pr), and 0.058 (Ln – Nd). The peculiarities of LPS for Sr3LnBIIITiO8 (BIII – Sc, In) have been analyzed, and the correlations between their composition and the constitution of LPS are found.